Impact of Food Intake, Ultrasound Transducer, Breathing Maneuvers and Body Position on Acoustic Radiation Force Impulse (ARFI) Elastometry of the Liver - Goertz, R. S.; Egger, C.; Neurath, M. F.; Strobel, D. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: Since acoustic radiation force impulse (ARFI) elastometry is an increasingly popular method for the assessment of hepatic fibrosis and cirrhosis, we investigated factors possibly influencing hepatic elastometric measurements. Materials and Methods: 30 healthy volunteers (17 females, 13 males) were recruited. The shear wave velocity of the right liver lobe was determined in a fasting upright and supine position and after different breathing maneuvers with the convex array (4C1) and in a supine position with the linear (9L4) ultrasound transducer. In 18 volunteers, subsequent measurements were obtained in a fasting state and 30, 60, 90 and 120 min after ingestion of a standardized breakfast. A group of 8 patients (average age: 76 years) with right heart insufficiency was also evaluated. Results: In the fasting state, the ARFI shear wave velocities measured in an upright position were significantly higher than those in supine position (p< 0.0001). The supine ARFI values were significantly higher with the linear transducer than with the convex transducer (p = 0.0034). The results in deep inspiration, deep expiration and during Valsalva maneuver showed no differences. The food intake-related ARFI elastometric measurements were significantly elevated at time points 30 min (p = 0.019) and 60 min (p = 0.036) postprandial. In right heart insufficiency, the ARFI values were elevated. Conclusion: Hepatic ARFI elastometry is a well evaluated method. A standardized examination should include measuring in a supine position with the convex transducer (4C1) without specific breathing maneuvers. Since ARFI elastometry values increase after food intake, measurements should be performed in the fasting state, or not earlier than 2 hours postprandially. Heart dysfunction may impair ARFI accuracy.
Keywords: ARFI; liver; meal; Valsalva; position